SPT6 regulates H3K14Ac deposition in mouse embryonic stem cells - Daixuan Zhang; Li Dong; Ying Cai; Peng Zhao; Qingqing Cai; Jian Zhang; Yajun Hu; Mandi Mu; Siyi Cheng; Jin Wang; Min Zeng; Chenxi He; et al. (Cell Reports)
Summary: SPT6 (suppressor of Ty 6) is a conserved histone chaperone that plays critical roles in RNA Pol II progression and nucleosome reassembly. However, the functions of SPT6 in chromatin regulation remain incompletely understood. Here, we show that SPT6 localizes to histone H3 lysine 14 acetylation (H3K14Ac)-enriched regions in mouse embryonic stem cells (mESCs). Loss of SPT6 leads to reduced H3K14Ac levels and diminished transcription. Mechanistically, we show that SPT6 enhances the chromatin binding of the acetyltransferases KAT7 and KAT6A/KAT6B, which are responsible for H3K14Ac deposition, but SPT6-facilitated H3K14Ac can also occur in a KAT7/6A/6B independent manner. Our findings highlight a vital role for SPT6 in preserving the H3K14Ac landscape in mESCs, providing new insights into the crosstalk between transcription machinery and H3K14Ac regulation in mammals.